An investigation into Safe Haven Assets precious metals and others - LI, SILE (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2018)
During the financial market turmoil of recent decades, asset classes tend to co-move more strongly, even without strong fundamental linkages, hence the contagion effect. A serious implication for portfolio management is that the benefits of diversification are reduced when they are needed the most. This motivates the search for ‘safe’ assets during market distress which would move against the falling markets. Gold’s reputation as a historical safe haven and other precious metals (i.e. silver, platinum and palladium’s) hedging ability in portfolio diversification motivate the investigation of whether silver, platinum and palladium have acted as safe haven across markets in periods of distress. This research firstly overviews the conceptual and theoretical aspects of safe haven assets, including its relationship with other market-linkages during market distress such as flight-to- safety. It then examines the safe haven properties of precious metals in eleven major world economies over the period 1994 to 2016. It finds that, on average, precious metals are weak safe haven about 33% of the time against stocks and 31% of the time against bonds, when asset returns fall below the lower 5% quantile range. Additionally, no precious metal provides safe haven status consistently over time or across asset classes. And, finally, strong safe haven is rare. The analysis then examines robust political, economic and financial determinants of precious metals as safe haven. Political risk is found to be a positive and robust determinant in most countries when gold is safe haven against stock and bond markets tail events. Stock volatility also sees positive and robust results across countries but only against stock market stress. Exchange rate, interest rate and credit spreads tend to have large coefficient values but results are quite mixed for different markets and not robust. Finally, inspired by recent studies on how investor attention could affect asset pricing, and the availability of online search data which is argued as a direct and new measure of investor attention, this research conducts spillover analysis between gold and safe haven currencies with their related search activities. It finds that, in general, spillovers from search volumes to returns are higher than spillovers from returns to search activities in the US, UK, Germany and China. Furthermore, the spillovers from searches to returns increase during market stress times in the recent decade.
APPROVED
Keywords: Precious metals; Safe haven assets; Market linkages; Flight-to-safety; Dependence measurement